Understanding the young generations' preference towards Malay traditional food in Malaysia - Abdul Ghafar Rahman, Suhailah; Ab Karim, Shahrim; Che Ishak, Farah Adibah; Arshad, Mohd Mursyid (Global Academic Excellence, 2018)
Every ethnic group in this world have their own uniqueness and one of the key component that contributed in shaping each ethnic group’s unique identity is their traditional foods which have been sustained and practiced for generations. Hence, traditional foods are viewed as a symbol of heritage to an ethnic group’s culture (Sharif, Zahari, Nor, and Muhammad, 2016b). This is true especially for Malaysia as this country is known for its diversified cultures. Nevertheless, the young generations nowadays do not seem to care about the importance of preserving their traditional foods. They are more likely to choose fast foods and convenience foods over traditional foods. Not only that, most of the young generations today do not know how to cook their own traditional foods anymore. This situation is very alarming as the ethnic groups in Malaysia might face the possibility of losing their heritage and unique identity. This article explores the factors that contributed to the changes of traditional foods consumptions and practices among the young generations in Malaysia within the Malay ethnic and Malay traditional food context. This article also discusses the role of family in preserving the Malay traditional food. The results are expected to highlight the significance of young generations role in continuing and sustaining Malay traditional food in Malaysia.